Selection of New City Locations in Al-Muthanna Governorate: Criteria and Indicators - Hassan, Zainab; Al-Shadidi, Hussain (Al-Adab Journal, 2025)
There is a necessity in establishing new cities in the continuous development of countries and population increase processes for two basic reasons:- First: To relieve population congestion and reduce the burden on all services, which have become of poor quality in the mother city and have led to the creation of multiple problems.-Second: Working to implement modern and creative ideas that start from scratch and that cannot be achieved in the Main city because they may have traditional characteristics and features that are difficult to change. Therefore, it is necessary to create new cities in order to develop and introduce innovative ideas with the characteristics of artificial intelligence."Therefore, in both cases, it is necessary to establish new cities with entirely different characteristics and standards from the main cities, not only in terms of design and planning but also in legal aspects that enforce strict regulations on everyone regarding the preservation of public properties, land use, and preventing encroachments across various sectors at the expense of others. Anyone who violates these laws should be penalized. These new cities can contribute to a more balanced distribution of resources in the country by allocating new strategic locations for the exploitation of natural resources or for developing new economic sectors. They will adopt modern technologies and smart solutions in delivering public services and managing resources efficiently, thus promoting innovation, development, and the application of sustainable development principles. After identifying the key planning criteria for the optimal spatial location of the new cities and comparing them with the proposed locations of the new cities in Al-Muthanna Governorate using the Analytic Hierarchy Process (AHP), it was found that the highest importance in terms of location is attributed to the new city of Al-Salman. This is due to its population capacity (size) of 96,000 people, the availability of a suitable economic base, the presence of surrounding towns and districts providing space for future expansions around the city, soil quality, and proximity to reliable water sources."